2022
DOI: 10.1123/ijspp.2022-0026
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Elite Youth Football Players’ Physiological State Using a Small-Sided Game: Associations With a Submaximal Running Test

Abstract: Purpose: To examine the utility of a standardized small-sided game (SSG) for monitoring within-player changes in mean exercise heart rate (HRex) when compared with a submaximal interval shuttle-run test (ISRT). Methods: Thirty-six elite youth football players (17 [1] y) took part in 6 test sessions across an in-season period (every 4 wk). Sessions consisted of the ISRT (20-m shuttles, 30″:15″ work:rest ratio, 70% maximal ISRT) followed by an SSG (7v7, 80 × 56 m, 6 min). HRex was collected during both protocols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
1
6
1
Order By: Relevance
“…Few practitioners reported using intermittent-variable SMFT, each adopting game-based formats (i.e., sided games). Although considered more feasible 16 , the control over the numerous contextual factors (e.g., number of players, tactics, rules) across assessments influencing locomotor outputs is likely prohibitive 17,18 . Such challenges may explain why few studies have used this practice longitudinally 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Few practitioners reported using intermittent-variable SMFT, each adopting game-based formats (i.e., sided games). Although considered more feasible 16 , the control over the numerous contextual factors (e.g., number of players, tactics, rules) across assessments influencing locomotor outputs is likely prohibitive 17,18 . Such challenges may explain why few studies have used this practice longitudinally 19 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the reported relationships were not excellent, and the researchers suggested this may be due to rarely occurring events during the sided-games (e.g., counterattacks) potentially lowering the standardisation of external load, subsequently influencing HRex. 8 Indeed, substantial within-athlete variability in HSR during sided-games was reported in a recent meta-analysis. 11 Although it is unrealistic to expect perfect associations between two materially different running assessments (i.e., continuous versus intermittent), monitoring HRex in passing or kicking drills (compared to sided-games) might allow for greater standardisation of external loads, possibly yielding closer associations with HRex during discrete SMFTs, and thereby providing improved insights into the physiological state.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, researchers have attempted to infer an athlete's physiological state in-situ by monitoring internal responses during intermittent-variable SMFTs. 8,9 These assessments, administered in the form of technical-tactical drills (e.g., sided-games), could potentially eliminate the need for discrete testing. For example, Lacome et al 9 reported that after controlling for external intensities, within-athlete changes in internal responses during soccer sided-games largely associated with HRex during a continuous-fixed SMFT (CF-SMFT) paced at 12 km•h -1 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations